Evaluation of the American Approach for Detecting Plan Irregularity - V. Alecci; M. De Stefano; S. Galassi; M. Lapi; M. Orlando (Advances in Civil Engineering)
The European seismic code 8 (Eurocode 8) classifies buildings as planwise regular according to four criteria which are mostly qualitative and a fifth one, which is based on parameters such as stiffness, eccentricity, and torsional radius, that can be only approximately defined for multistory buildings. Therefore, such plan-regularity criteria are in need of improvement. ASCE seismic code, according to a different criterion, considers plan (or “torsional”) irregularity in a building when the maximum story drift, at one end of the structure, exceeds more than 1.2 times the average of the story drifts at the two ends of the structure under equivalent static analysis. Nevertheless, both the ASCE approach and the threshold value of 1.2 need to be supported by adequate background studies, based also on nonlinear seismic analysis. In this paper, a numerical analysis is carried out, by studying the seismic response of an existing R/C school building taken as the reference structure. Linear static analysis is developed by progressively shifting the centre of mass, until the ratio between the maximum lateral displacement of the floor at the level is considered and the average of the horizontal displacements at extreme positions of the floor at the same level matches and even exceeds the value of 1.2. Then, nonlinear dynamic analyses are carried out to check the corresponding level of response irregularity in terms of uneven plan distribution of deformation and displacement demands and performance parameters. The above comparison leads to check the suitability of the ASCE approach and, in particular, of the threshold value of 1.2 for identifying buildings plan irregularity.